2022
DOI: 10.1371/journal.pone.0267019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of breast muscle myopathies (spaghetti meat, woody breast, white striping) and associated risk factors in broiler chickens from Ontario Canada

Abstract: Spaghetti meat (SM), woody breast (WB), and white striping (WS) are myopathies that affect the pectoral muscle of fast-growing broiler chickens. The prevalence and possible risk factors of these myopathies have been reported in other countries, but not yet in Canada. Thus, the objective of this study was to assess the prevalence and risk factors associated with these myopathies in a representative population of Canadian broilers. From May 2019 to March 2020, 250 random breast fillets from each of 37 flocks (to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 61 publications
6
36
0
Order By: Relevance
“…Reports by Lorenzi et al (2014) described a prevalence of 43.1% of WS fillets which reached 60.3% in broilers with higher slaughter weight. More recent reports (Petracci et al, 2019;Che et al, 2022b) showed high WS occurrence (>90%) which could be partly attributed to increased awareness of the issue and invested efforts to monitor and better understand the etiology and mechanisms leading to myopathies occurrence (Soglia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports by Lorenzi et al (2014) described a prevalence of 43.1% of WS fillets which reached 60.3% in broilers with higher slaughter weight. More recent reports (Petracci et al, 2019;Che et al, 2022b) showed high WS occurrence (>90%) which could be partly attributed to increased awareness of the issue and invested efforts to monitor and better understand the etiology and mechanisms leading to myopathies occurrence (Soglia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As for the other myopathies, relating flock data of growth to individual data of myopathy, Che et al (2022b) recently found that increased live weight is a risk factor for both WB and SM occurrence. Stated the high correlation between slaughter weight and daily weight gain in our data set (R 2 : 0.86; data not reported in tables), this result is consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations